Analisis Interpretatif Peran Boyband Seventeen dalam Pembentukan Identitas dan Perilaku Konsumtif CARAT Medan - Wardani, Ayu; Zuhriah, Zuhriah (Universitas Syiah Kuala, 2025)
This study aims to examine the interpretative role of the Korean boyband Seventeen in shaping identity and consumptive behavior within the CARAT fandom community in Medan. The K-Pop phenomenon as a global cultural force not only influences entertainment but also constructs the personal and social identities of its fans. This research employed a qualitative descriptiveinterpretative approach, with data collected through in-depth interviews, community observations, and documentation of related cultural products. Data analysis was carried out thematically and semiotically to uncover patterns of meaning, symbols, and communicative processes within fandom interactions. The findings reveal that being a CARAT is perceived not merely as a fan identity but as an integral part of self-concept, providing emotional support, social belonging, and motivation. Values promoted by Seventeen, such as hard work, solidarity, empathy, and perseverance, are internalized by fans and reflected in their daily behavior. Consumptive practices, including the purchase of albums, merchandise, and event participation, are understood not only as economic transactions but also as symbolic expressions of identity and social status. The CARAT Medan community plays a vital role as a reference group that negotiates identity while moderating consumer behavior by promoting financial awareness and ethical consumption, thus preventing social or economic pressure. The study concludes that fandom identity is a dynamic social construction that functions as a space for self-affirmation, personal development, and responsible consumption, highlighting that K-Pop fandoms are not merely entertainment spaces but also arenas for identity formation and ethical, sustainable consumer practices.